PENGARUH METODE PEMBELAJARAN DAN MOTIVASI BELAJAR TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN BAHASA ARAB SISWA KELAS XI SMAM 1 KOTA BENGKULU - Rosi Delta Fitrianah (IAIN Bengkulu, 2018)
This research aims: 1) To know the effect of teaching methods to the learning outcomes of students in the subjects of Arabic. 2.) The effect of learning motivation to the learning outcomes of students in the subjects of Arabic. 3.) The influence of teaching methods and learning motivation toward learning outcomes of students in the subjects of Arabic. The method used in this research is the experimental method, the population in this study were students of class XI SMA Muhammadiyah 1. Me- chanical Penambilan samples in this study is teknikrandom sampling, choose two classes of random sampling from four classes sampled. Class XI IPS was selected as an experimental class B and class XI IPS C was chosen as the control class. There are differences in learning outcomes Arabic among students taught using learning methods and methods suggestopedia eclectic. Evidenced by student learning outcomes in the application of an electric method is better than the application of the method suggestopedia. Evidenced by student learning outcomes in the application of methods elektiklebih better than the application of the method shown in the ANOVA suggestopedia 1 lines sig = 0.001 <0.05. There are differences between students who have high motivation for learning outcomes Arabic better than students who have low motivation seen in the ANOVA one lane sig =0.252 <0.05. There is the influence of learning with students’ motivation to learn Arabic results it is seen in the second ANOVAtest track at 4:12 table obtained sig = 0.088 therefore sigma probability greater than 0.05, the null hypothesis is accepted